Determinants of Profitability in Bank Syariah Indonesia Post-Merger: an Empirical Analysis of CAR, BOPO, and NPF on ROA During 2021–2024 - Hartanti, Hartanti; Ratiyah, Ratiyah; Setyaningsih, Eka Dyah; Imelda Sari (Jurnal Multidisiplin Sahombu, 2025)
This study examines the profitability performance of Bank Syariah Indonesia during the post-merger period by analyzing the influence of capital strength, operational efficiency, and financing quality on the return generated from total assets. A quantitative approach is employed using secondary financial data obtained from official publications to evaluate the relationship among key internal banking indicators. The analysis reveals a consistent improvement in profitability that aligns with enhanced efficiency and stronger risk management practices. Operational efficiency demonstrates the strongest contribution to profitability, while financing quality also shows a substantial effect through its role in managing credit risk. Capital strength exhibits a positive yet relatively limited influence, suggesting that excess capital may not always translate into higher earning capacity. The findings highlight the importance of digital transformation, disciplined cost management, and prudent financing strategies in sustaining the financial performance of Islamic banks in a competitive environment.